Pengaruh Metode Latihan Agility Hurdle Drills dan Latihan Agility Ring Drills terhadap Permainan Sepak Bola Peserta Ekstrakurikuler di MA Al-Fuqron Pampangan - Yogi Seven Saputra; Dessy Wardiah; Jujur Gunawan Manullang (Asosiasi Riset Ilmu Pendidikan Indonesia, 2024)
This study aims to evaluate the effect of Agility Hurdle Drills and Agility Ring Drills on increasing the agility of students who take part in soccer extracurriculars at MA Al-Furqon Pampangan. Agility is a very important physical ability in the game of soccer, especially in fast movement, changing direction, and avoiding opponents. This research used a Pretest-Posttest Control Group design with research subjects of 25 students divided into two groups. The first group was given training using the Agility Hurdle Drills method, while the second group used the Agility Ring Drills method. The training program was carried out over 16 meetings, and students' agility was measured using a shuttle run test before (pre-test) and after (post-test) the training program. The research results showed that both training methods provided a significant increase in students' agility, as proven through statistical analysis. Although both methods were effective, there was variation in agility gains among participants, indicating the need for a more personalized approach to training. This research provides evidence that Agility Hurdle Drills and Agility Ring Drills are effective methods in improving student agility, and can be implemented in other soccer training programs to improve player performance.